2020
DOI: 10.1093/eurheartj/ehaa794
|View full text |Cite
|
Sign up to set email alerts
|

Hypertension and renin-angiotensin system blockers are not associated with expression of angiotensin-converting enzyme 2 (ACE2) in the kidney

Abstract: Aims Angiotensin-converting enzyme 2 (ACE2) is the cellular entry point for severe acute respiratory syndrome coronavirus (SARS-CoV-2)—the cause of coronavirus disease 2019 (COVID-19). However, the effect of renin-angiotensin system (RAS)-inhibition on ACE2 expression in human tissues of key relevance to blood pressure regulation and COVID-19 infection has not previously been reported. Methods and results We examined how hype… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
54
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(56 citation statements)
references
References 58 publications
2
54
0
Order By: Relevance
“…In 221 hypertensive patients, no association between the use of βARBs and renal ACE2 gene expression was found (X. Jiang et al, 2020 ). In the context of COVID-19, a recent study with 880 COVID-19 patients reported that the use of βARBs was associated with a significantly better outcome ( Pinto-Sietsma et al, 2020 ).…”
Section: Cardiovascular Drugs and Ace2mentioning
confidence: 99%
See 1 more Smart Citation
“…In 221 hypertensive patients, no association between the use of βARBs and renal ACE2 gene expression was found (X. Jiang et al, 2020 ). In the context of COVID-19, a recent study with 880 COVID-19 patients reported that the use of βARBs was associated with a significantly better outcome ( Pinto-Sietsma et al, 2020 ).…”
Section: Cardiovascular Drugs and Ace2mentioning
confidence: 99%
“…or ARBs and renal ACE2 gene expression was found (X. Jiang et al, 2020 ). In addition, in kidney biopsies from 49 diabetic patients, treatment with ARBs and ACE-Inhs.…”
Section: Cardiovascular Drugs and Ace2mentioning
confidence: 99%
“…There is no correlation between ACE-Is/ARBs and AKI. Meanwhile, neither of them can increase the expression of ACE2 in the human kidney ( Jiang et al, 2020 ; Tetlow et al, 2020 ). CD147, also named EMMPRIN, is involved in tumor development, plasmodium invasion and virus infection ( Castro et al, 2003 ; Chen et al, 2005 ; Lu et al, 2018 ).…”
Section: Pathogenesis Of Acute Kidney Injury In Covid-19mentioning
confidence: 99%
“…The irony is, that alongside these RCTs, we have also discovered that the COVID-19 RAS-inhibition controversy was most likely ill-founded in the first place, as recent data suggest that these drugs do not seem to increase ACE2 expression, especially in the lung, after all. 10 , 11 …”
mentioning
confidence: 99%